Producción de nanopartículas de PLGA por el método de emulsión y evaporación para encapsular N-Acetilcisteína (NAC) - Lancheros, Ruth J.; Grupo de Investigación en Procesos Químicos y Bioquímicos, Departamento de Ingeniería Química y Ambiental, Universidad Nacional de Colombia, Bogotá, Colombia. (2014)
Lactic and glycolic acid (PLGA) copolymer nanoparticles of less than 200 nm were produced to trap and transport N acetylcysteine (NAC) to be used in future applications, in the field of drug delivery systems. To do this, we selected the simple emulsion and evaporation method, using ethyl acetate as a solvent, Pluronic F127® as a surfactant, water and used ultrasound to generate the emulsion. The effect of the parameters during the organic to the aqueous phase was assessed as well as the amplitude and sonication. We found nanoparticles of 114 nm that trapped colloidally stable 15% NAC; the ratio of organic to the aqueous phase was 1 to 5, the amplitude 60% and the ultrasound period was 60 s.